POP-UP BOOK METHOD IN TEACHING READING SKILLS - Khofifah Ade Saputri; Muthmainnah Mursidin; Sulviana Sulviana (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
The aim of this research present at determining; 1) the use of pop-up books improve students’s reading skills. 2) the students’ interests in using the pop-up book for reading skills. The subjects of this study were the students of the seventh-grade SMP Laniang Makassar totaling 15 students. The research used a pre-exprimental research design with a one group pre-test and post-test design and used two instruments. The tests carried out included pre-test, post-test and questionnaire. Data were collected through tests.. Based the result of the data after obtaining test scores and processed using the T-test formula in SPSS version 25. The results of this study were the average score of reading skill obtained by students sthrough the pre-test was 38.00 and post-test was 74.00 with sig (2-tailed) value is 0.00 < 0.05. Thos shows that Ho is rejected and Ha is accepted. So that, teaching reading skills using Pop-Up Book could improve reading skill students.